The impact of the COVID-19 pandemic on harm reduction services in Catalonia: the experience of people who use drugs and harm reduction professionals - Mar Bosch-Arís; Laia Gasulla; Teresa de Gispert; Lidia Segura; Joan Colom (BMC, 2022)
Abstract Background Harm reduction services and professionals have had to reorganise and adapt to COVID-19 prevention measures while still ensuring health and social services for people who use drugs (PUD). Objective To assess the impact of the COVID-19 pandemic on PUD and on the professionals who provide harm reduction services. Methods A qualitative, exploratory, multicentre design was used. Two focus groups were held with harm reduction professionals, and 40 individual semi-structured interviews were undertaken with PUD in various harm reduction services in Catalonia. Interviews and focus group discussions were transcribed and analysed using thematic content analysis. Results Harm reduction services adapted to the pandemic situation by employing methods such as reducing opening hours and closing drop in areas, along with health protection measures such as access control, which in turn led to stress among both professionals and service users. Despite the changes implemented, PUD continued to have access to sterile drug use equipment and methadone treatment. In addition, those who were not in treatment were able to access it rapidly. Regarding their emotional state, the PUD reported that it was worse during the pandemic than before the lockdown, with women affected to a greater extent than men. The harm reduction professionals reported difficulties in managing service users' compliance with the security measures at the beginning of the lockdown and having had to focus primarily on providing food and shelter for the PUD. Conclusions It is important to keep PUD in mind and maintain a harm reduction perspective when implementing confinement measures in situations such as those experienced during the COVID pandemic. Guaranteeing that PUD have their basic needs such as food, hygiene and shelter covered is key.